Branching coral as a macroalgal refuge in a marginal coral reef system - Bennett, Scott; Vergés, A.; Bellwood, D. (Springer Verlag, 2010)
Marginal coral reef systems may provide valuable insights into the nature of ecosystem processes in systems on the trajectory towards a phase shift to an alternate ecosystem state. This study investigates the process of herbivory in a marginal coral reef system in the Keppel Islands at the southern end of the Great Barrier Reef. Branching Acropora coral and the brown macroalga Lobophora variegata occupied up to 95% of the reef crest substratum at the three surveyed reefs. Feeding rates of herbivorous fishes and removal rates of Lobophora were directly quantified within areas of branching Acropora and on planar surfaces. Feeding rates by herbivorous fishes were habitat dependent with the highest bite rates being found in planar habitats for both Lobophora and the epilithic algal matrix (EAM) by 1-2 orders of magnitude, respectively. Feeding rates on Lobophora were, however, much lower than rates on the EAM. The low rates of Lobophora removal and significantly lower rates of herbivory in branching habitats were consistent with the high biomass of this brown alga throughout the Keppel Islands and with its distribution on reef crests, where Lobophora biomass was 20 times greater in branching than in planar habitats. This lack of feeding by herbivorous fishes within branching coral habitats in the Keppel Islands contrasts with the typical role of coral and topographic complexity on herbivores on coral reefs and highlights the potential for complex interactions between algae, corals and fishes on coral reefs. On marginal systems, herbivory may modify algal distributions but may be unable to contain the proliferation of algae such as Lobophora. © Springer-Verlag 2010.